Rapid and Structurally Diverse Synthesis of Multi‐Substituted β‐Keto Amide Derivatives Based on a Dioxinone Scaffold. Issue 22 (23rd June 2014) - Fuse, Shinichiro; Yoshida, Hayato; Oosumi, Kazuya; Takahashi, Takashi
Abstract: A sequential diversification approach for the synthesis of various multi‐substituted β‐keto amide derivatives based on a simple and readily available dioxinone scaffold was developed. The process involves: (1) nucleophilic addition of the scaffold to an aldehyde, and a subsequent one‐pot dehydration; (2) palladium‐catalysed cross‐coupling of the scaffold with either an arylboronic acid pinacol ester, or CO and an aliphatic amine; and (3) nucleophilic addition of either an aliphatic amine or an arylamine, or a hetero‐Diels–Alder reaction of isocyanate/isothiocyanate, with an acylketene generated in situ from the dioxinone scaffold. Abstract : Multi‐substituted β‐keto amides were synthesized in a sequential four‐component coupling process based on a dioxinone scaffold. The sequence consists of three steps: (1) nucleophilic addition of the scaffold to R 1 –CHO followed by a one‐pot dehydration; (2) Pd‐catalysed coupling of the scaffold with either R 2 –[B] or CO and R 2 –NH2 ; (3) nucleophilic addition of R 3 –NH2 to an in situ generated acyl ketene.